The co-construction of a bilingual glossary of terms for engineering design technologies as part of learning in engineering trough a collaborative CLIL approach - Gaspar, Marcelo (2018)
This case study refers to the collaborative work of pre-engineering and engineering students, supported by their content and English for Specific Purposes (ESP) teachers, on the development of a full semester assignment focusing on the design and construction of a dedicated glossary of terms. Based on a student-centered Content and Language Integrated Learning (CLIL) approach, intermediate tasks were proposed to the students to construct their own personal glossary about the subject. As a result of the combined effort of all actors, a full class bilingual glossary of terms was obtained for engineering design technologies as part of learning in engineering through a collaborative CLIL approach.